A Gazeta e o Estadão - Gebara, Ademir (Anais do Museu Paulista: História e Cultura Material, 1978)
The main purpose of this paper is to study the beginning of the Republican press in Campinas. Two newspapers are particulary focused in this study: Gazeta de Campinas, and O Constitucional, which represent different political trends. The most important problem we intend to solve throughout the paper refers to the centralization of Republican propaganda in São Paulo, with the foundation in 1874/1875 of the newspaper A Província de São Paulo. This altered the patterns of political action of the provincial press. We explain how these changes were expressed by the newspaper which was the center of republican propaganda in the city of Campinas.